Analysis of Errors in Paragraph Writing in English by Second Year Geography & History Students at University of Baghdad (Journal of the College of Education for Women, 2019)
This study focuses on the writing skill which is a social act .Students need to expressthemselves in writing, but students of History and Geography departments are poor inwriting. This study aims at identifying and classifying the errors committed by thestudents, and then giving remedies.Writing can be considered as a channel or as a goal of language learning.Students learn to write in a foreign language. Writing as a goal basically focuses onthe development of writing skills to fulfill such purposes as note-taking, summarizing,narrating, reporting and replying required for various real-life situation(Mechalakelli,2007)Students at Departments of Geography and History study English as a part oftheir syllabus requirement in the College of Education for Women. The researcherrealizes that it is important to improve students' skills in writing because it is animportant tool to their profession and for further education in the future. Therefore,this study is an attempt to evaluate the writing skills of the second class eveningstudents (History and Geography)Departments.The students are asked to write a paragraph on topics based on their readingpassages, chosen from their prescribed textbooks. They had been trained to constructa well- organized paragraph in their preparatory schools for three years until theirgraduation. Hence, the study attempts to find the students' errors in their writing inEnglish.